(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the psychological factors of the formation of altruistic competencies in the digital environment. Currently, digital technologies have a significant impact on the formation of social relationships, forms of communication and values ​​between people. Therefore, the formation of young people as socially responsible, empathetic and ready to help others in the digital space is one of the important issues. Also, empathy, social identification, motivation and communicative skills are analyzed as important factors in the development of altruistic competencies.